PEMANFAATAN KOLEKSI BIDANG ILMU KOMPUTER PADA PERPUSTAKAAN AKADEMI MANAJEMEN INFORMATIKA KOMPUTER HARAPAN MEDAN - azharryandi arman (Jurnal Pustaka Nusantara dan Budaya, 2013)
Results of research conducted in the library Akademi Manajemen Informatika Komputer Harapan Medan aims to determine the level of applicability collection of computer science. The number of member in library Akademi Manajemen Informatika Komputer Harapan Medan as many as 158 people sampled 25% or of 40 people from the membership 'overall. Engineering studies using techniques accidental by distributing questionnaires to library users. Users come to the library 1 or 2 times a week to complete the tasks assigned faculty. Search catalog information using manual and assisted librarians.